VD_FINDINFO Décision / 2020 / 1053 vom 19. Oktober 2020 - VD Tribunal cantonal (2020)
INDEMNITÉEN GÉNÉRAL, AVOCAT D'OFFICE, DOMMAGE, CLASSEMENT DE LA PROCÉDURE | 135 CPP (CH), 319 CPP (CH), 429 al. 1 let. c CPP (CH)